Handbook of Research on ICT-Enabled Transformational Government 2009
DOI: 10.4018/978-1-60566-390-6.ch025
|View full text |Cite
|
Sign up to set email alerts
|

IT Governance in the Public Sector in a Developing Country

Abstract: This chapter focuses on IT governance in the public sector organizations in a developing country like Tanzania. Today in many organizations in the public sector, the use of IT has become crucial in sustaining and extending the organizations’ strategies and objectives. This pervasive use of technology has caused a critical dependency on IT that calls for a specific focus on IT governance. In this chapter, we provide its overview and, based on the analysis of five case studies indicate the current practices, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 4 publications
2
17
1
Order By: Relevance
“…The organizations should appraise existing framework or best practices with their organizational processes before adoption (Krey et al, 2010). For IT governance adoption in developing nation (Tanzania), Nfuka et al (2009) highlighted that the problems with IT governance in public sector are lack of a specific IT strategic plan, lack of clear roles and responsibilities, inadequate follow-up and enforcement mechanisms, lack of IT governance awareness, inadequate budget, and lack of IT professional skills. In summary, the research in this category commonly reflects the issues of logical coherence for implementing IT governance into the organizational context.…”
Section: It Governance Framework Development and Guidelinementioning
confidence: 99%
“…The organizations should appraise existing framework or best practices with their organizational processes before adoption (Krey et al, 2010). For IT governance adoption in developing nation (Tanzania), Nfuka et al (2009) highlighted that the problems with IT governance in public sector are lack of a specific IT strategic plan, lack of clear roles and responsibilities, inadequate follow-up and enforcement mechanisms, lack of IT governance awareness, inadequate budget, and lack of IT professional skills. In summary, the research in this category commonly reflects the issues of logical coherence for implementing IT governance into the organizational context.…”
Section: It Governance Framework Development and Guidelinementioning
confidence: 99%
“…Unfortunately, structured and well-organized practices for ITSM-such as those described in ITIL-are rarely achieved in organizations of developing countries, [1,11,18,21,36,38,42]. The reasons vary, but the most common challenges are related to the lack of a proper ICT policy and the low level of IT professionalism.…”
Section: Tier 1: Ict Services Of An Organizationmentioning
confidence: 99%
“…(2011) indicated that although both developing and developed countries share similar barriers to IT governance, there exist some distinctive factors such as lack of regulatory environment, lack of industry and vendor support, and national culture that hinder IT governance in developing nations. The industry sector plays a major role in the adoption of ITG practices and much effort has been spent investigating IT governance in organizations (De Haes & Van Grembergen, 2009;Nfuka et al, 2009;Othman et al, 2011). IT supports invariably all sectors of an economy including service, manufacturing, agriculture, and mining.…”
Section: Introductionmentioning
confidence: 99%